From specimen to witness: redefining exhibits’ values in design museums - Valeria Burgio (piano b, 2016)
Rapid Response Collecting is part of the collecting activities of the Victoria and Albert Museum in London. The curators of this project select objects that are apparently banal and not very meaningful and exhibit them in a special section of the museum, which is nevertheless part of the Contemporary Product Design area. Their aim is to recall media events from the next past. The exhibition design is a mise-en-récit activating both personal and collective narratives through the exhibits. Moreover, it demands the viewer to observe an everyday object through an alienated sight as if it belonged to another culture. This case-study is the point of departure to reflect on the semiotic status of the exhibit in a design museum: most times, this is a sample of an object produced in series, becoming the trigger for a reflection on technological and social innovation. Thus, the object shows a “specific identity” connecting the sample to a model (Goodman 1976, Prieto 1988). In other cases, though still being a sample of an object produced in series, the exhibit shows a special and material connection with an event: the object can be thus considered a witness, because it has been touched by history and its main characters and can condense it in a simple material form. Authenticity has a different gradation depending on the kind of object that is examined; it becomes a rhetorical strategy, which is connected with forms of validation of the proof, whose final aim is to re-enact the event. The object can indeed be a simple pretext to tell a story, though not acquiring any value in itself, keeping being replaceable and valueless. Otherwise, the object can be presented as a unique occurrence showing on its body the traces of the event, endowed with the aura of uniqueness which is typical of the artwork.